Genetics of Familial Hypercholesterolemia - Ziske Maritska; Aditya Rafrenda; Amirah Adillah; Balqis Wulandari; Endah Rahmadani; Ernes Putra Gunawan; Khumaisiyah Khumaisiyah; Nur Rakhman Pratama; Trizky Nataza Putra (Biomedical Journal of Indonesia, 2023)
Cholesterol is a necessary component of numerous physiologic processes that must be strictly regulated. Multiple genetic disorders, such as Familial Hypercholesterolemia, frequently induce dysfunctional cholesterol metabolism. Familial hypercholesterolemia (FH) is a frequent hereditary autosomal co-dominant marked by disarray by increased plasma amounts of low-density lipoprotein (LDL) cholesterol and premature cardiovascular disease. Familial Hypercholesterolemia (FH) is increasing but often remains underdiagnosed. This review aims to outline existing information on Familial Hypercholesterolemia with a focus on genetics, diagnostic strategies, treatments, and guidelines for management.